PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT REHOBAT SRINGIN - Alvina Kusumaningrum; Rauly Sijabat; Bayu Kurniawan (CV. Denasya Smart Publisher, 2024)
This study aims to determine the influence of organizational culture, motivation and work environment on employee performance at PT. Rehobat Sringin. This study uses a quantitative research method. The population in this study was 155 populations taken from several divisions, namely from the owner 1 person, office staff 1 person, field workers 59 people. In this study, the selected population was 155 employees. The findings in this study are that organizational culture has a positive and significant effect on employee performance at PT. Rehobat Sringin, the work environment has a positive and significant effect on employee performance at PT. Rehobat Sringin, testing shows that work motivation has a positive and significant effect on employee performance at PT. Rehobat Sringin.